THE EFFECT OF HEALTH SERVICE QUALITY ON THE LEVEL OF SATISFACTION OF INPATIENTS AT BHAYANGKARA TK.II HOSPITAL BALIKPAPAN - Rivaldi, Achmad; Imam Suprapto, Sentot; Wardani, Ratna (The SDGS Forum Communication, 2025)
Quality healthcare services are a key factor in determining patient satisfaction levels, especially for hospitals competing to provide the best services. This study aims to analyze the impact of healthcare service quality on inpatient satisfaction at Bhayangkara Level II Hospital Balikpapan. The study employs a quantitative method with a descriptive approach. The research sample consists of 115 inpatients selected using a purposive sampling technique. The results indicate that physical evidence and reliability do not have a significant impact on patient satisfaction, with significance values greater than 0.05. Meanwhile, responsiveness, assurance, and empathy have a positive and significant effect on patient satisfaction, with significance values less than 0.05. This finding confirms that patient satisfaction is more influenced by healthcare workers' responsiveness, service assurance, and empathetic interactions with patients rather than physical facilities or procedural reliability. Therefore, improving healthcare service quality at Bhayangkara Level II Hospital Balikpapan should focus on enhancing communication, healthcare workers' skills, and providing a sense of security to patients to increase their satisfaction